Summer and winter sensitivity of leaves and xylem to minimum freezing temperatures: a comparison of co-occurring Mediterranean oaks that differ in leaf lifespan. - Cavender-Bares, J; Cortés, P; Rambal, S; Joffre, R; Miles, B; Rocheteau, A (The New phytologist, 2005)
Freezing sensitivity of leaves and xylem was examined in four co-occurring Mediterranean oaks (Quercus spp.) grown in a common garden to determine whether freezing responses of leaves and xylem were coordinated and could be predicted by leaf lifespan. Freezing-induced embolism and loss of photosynthetic function were measured after overnight exposure to a range of subzero temperatures in both summer and winter. Both measures were found to be dependent on minimum freezing temperature and were correlated with leaf lifespan and vessel diameter. The dependence of xylem embolism on minimum freezing temperature may result from the decline in water potential with ice temperature that influences the redistribution of water during freezing and leads to an increase in xylem tension. Winter acclimatization had a relatively small effect on the vulnerability to freezing-induced embolism, although leaf photosynthetic function showed a strong acclimatization response, particularly in the two evergreen species. Quercus ilex, the species with the longest leaf lifespan and narrowest vessel diameters, showed the highest freezing tolerance. This helps explain its ability to inhabit a broad range throughout the Mediterranean region. By contrast, the inability of the deciduous oaks to maintain photosynthetic and vascular function throughout the winter indicates a competitive disadvantage that may prevent them from expanding their ranges.
Keywords: cold acclimatization; decline in F V /F M; freezing-induced embolism; leaf lifespan; minimum temperatures; xylem anatomy